Priority for Handling Accident Prone Locations on National Road - Triawan, Fajar; Susilo, Budi Hartanto (Jurnal Teknik Sipil, 2023)
The length of the national road of the Central Java Province is 1,518.09 km with a road stability status of 98.06%. Victims due to accidents in Central Java Province according to Central Java Regional Police data for 3 (three) consecutive years: in 2018 the number of victims was 26,209 people, in 2019 the number of victims was 34,792 people, in 2020 the number of victims was 28,051 people. The impact is the cost of the accident and for victims and their families as a result of traffic accidents. The purpose of this study is to identify Accident Prone Locations on national roads by providing input in the framework of planning the national road preservation program. The method used in this study is the Accident Equivalent Number Method and The Gross Output with road preservation costs. Priority LRK on the north cross-national road in 2019 was 10 LRK, 2020 was 11 LRK and 2021 was 10 LRK. The results of BBKE calculations on Priority LRK in 2019 was IDR396.265.433.024, in 2020 was IDR368.855.844.549, and in 2021 was IDR417.424.376.692. In general, the handling of Priority LRK has not been accommodated in the implementation of national road preservation. The preparation of the national road network preservation program and budget is integrated into the road safety program, namely the handling of Priority LRK.